MOTIVASI PETANI DALAM USAHA TANI DI KOTA MALANG - Farah Mutiara; Dwi Asnawi Nurhananto (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2021)
Motivation is not just fulfilling the needs of farmers' lives but also the provision of other supporting facilities such as agricultural production facilities. The government also has a positive effect, because in general farmers will be happy with government leaders who always pay attention to the needs of farmers, especially rice farmers, so that all of them can motivate farmers to work with enthusiasm. The purpose of this study is for the purpose of this study which is as follows: (1) Analyzing what factors are affect the motivation of farmers in increase rice production in the Tlogomas Sub-District, Malang City. Analysis of the data used The writer in this research is Descriptive method and Likert’s Scale Summated Rating (SLR). The results showed that motivation factors consisted of internal and external factors. Where the biggest score on internal factors is length of effort (4.93), while the biggest external factor is the intensity of extension activities (4,26).